American alligators (Alligator mississippiensis) as wetland ecosystem carbon stock regulators - Christopher M. Murray; Tyler Steven Coleman; Wray Gabel; Ken W. Krauss (Scientific Reports, 2025)
Abstract Blue carbon refers to organic carbon sequestered by oceanic and coastal ecosystems. This stock has gained global attention as a high organic carbon repository relative to other ecosystems. Within blue carbon ecosystems, tidally influenced wetlands alone store a disproportionately higher amount of organic carbon than other blue carbon systems. North America harbors 42% of tidally influenced global wetland area, which has been identified as a critical carbon stock in the context of climate change mitigation. However, quantified associations between vertebrate biota and carbon sequestration within ecosystems are in their infancy and have been incidental, given that microbial trophic levels are thought to drive nutrient dynamics. Here, we assess the relationship between American alligator (Alligator mississippiensis) demography and tidally influenced wetland soil carbon stock among habitats at continental, biogeographically-relevant, and local scales. We used soil core profile data from the Smithsonian’s Coastal Carbon Network and filtered for continuous core profiles in tidally influenced wetland areas along the Gulf and Atlantic Coasts of the United States. Results indicate that American alligator presence is positively correlated with soil carbon stock across habitats within their native distribution. Further, American alligator demographic variables are positively correlated with soil carbon stock at local scales. These conclusions are concordant with previous findings that apex predators, through trophic cascade theory, play a key role in regulating soil carbon stock and that alligators are functional apex predators in carbon dynamics and a key commercialized natural resource.